Crossover magnetoresistance in non-transferred synthesized graphdiyne film. (30th October 2021) - Kang, Huifang; Hua, Binchang; Xu, Lanqing; Zhan, Xiaoling; Zheng, Yongping; Huang, Zhigao
Abstract: Two-dimensional layered carbon materials such as graphene constructed by sp 2 hybridization have raised considerable interest due to their large, non-saturating magnetoresistance. As a new sp - sp 2 hybridization structure layered carbon material, the transport performance of graphdiyne has been founded comparable with graphene, while the magnetoresistance remains to be clarified. In this work, we developed a modified non-transferred graphdiyne film synthesized method and studied its magnetoresistance effect. We observed an unexpected temperature-dependent crossover between positive and negative magnetoresistance in graphdiyne film. The film shows negative magnetoresistance at 5–19 K, the maximum intensity of the negative magnetoresistance was about 150% at 5 K under 3 T magnetic field. It presents positive magnetoresistance at 19–21 K under 3 T magnetic field, the magnetoresistance value reached 150% at 20 K. The mechanism of crossover positive and negative magnetoresistance originates from a superposition of the magnetic polaron model and weak localization. Graphical abstract: Image 1 Highlights: ● Developed a modified non-transferred graphdiyne film synthesis method grown on an arbitrary substrate. ● Crossover positive and negative magnetoresistance was observed in graphdiyne film. ● Graphdiyne film presents maximum value of 150% in positive magnetoresistance (PMR), and 150% in negative magnetoresistance.